Construct method of predicting satisfaction model of customer requirements based on product technical characteristics. (1st January 2012) - Yang, Xiaoan; Cao, Hongkui; Liu, Huifen; Deng, Qian
To deal with product technical characteristics configuration of customer requirements is one key links of product design process. In order to improve customer satisfactions for product, relationship for mapping between customer requirements and product technical characteristics needed to be analysed and objective relatively mapping model to be constructed. A novel approach based on customer satisfactions information digging from case products and satisfaction information of expert technical characteristics was put forward in this paper. Technical characteristics evaluation values were expressed by rough number, technical characteristics target sequence was determined on the basis of efficiency, cost type and middle type in this method, then the deviation and satisfaction between technical characteristics evaluation values and target sequence were calculated, finally measuring satisfaction degree from customer to the various requirements of case products according to seven cascades. Take the satisfactions of customers and technical characteristics of 16 electric bicycles as training samples of BP network, put into use MATLAB software simulation to obtain the mapping model of customer requirements and technical characteristics, which could predict customer requirements satisfaction degree corresponding with technical characteristic configuration of product design schemes.